The Urgency of Implementing Illicit Enrichment Regulations in Eradicing Corruption in Indonesia - Juang Intan Pratiwi; Arief Fahmi Lubis (Westscience Press, 2023)
Corruption cases in Indonesia are very widespread and even always increase every year. In Indonesia itself, there are regulations regarding corruption, namely the Corruption Law, the TPPK Law, the TPPU Law and other related regulations. However, these regulations are still not able to provide maximum handling. Because it places more emphasis on punishing the perpetrators and has not maximized the recovery of state financial losses. For this reason, a regulation is needed to be able to deal with corruption in Indonesia and optimize the recovery of state financial losses or the return of corrupted assets. Illicit Enrichment is a rule regarding the illegal or unfair wealth of public officials compared to their income. Illicit Enrichment is regulated in the UNCAC convention which was ratified by the United Nations in Mexico and Indonesia is a participating country in the convention as well as ratifying the UNCAC convention. However, until now in Indonesia in the regulations regarding criminal acts of corruption there are still no rules regarding Illicit Enrichment. The urgency of regulation regarding illegitimate assets must be established in Indonesia because the orientation of handling them is to optimize the return of corrupted assets. Illicit Enrichment does not only look at the assets of corruptors who are allegedly related to alleged corruption, but also looks at the entire wealth of public officials, whether this wealth can be accounted for or not.